2016
DOI: 10.1016/j.cbi.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Bothriurus bonariensis scorpion venom activates voltage-dependent sodium channels in insect and mammalian nervous systems

Abstract: Animal venoms have been widely recognized as a major source of biologically active molecules. Bothriurus bonariensis, popularly known as black scorpion, is the arthropod responsible for the highest number of accidents involving scorpion sting in Southern Brazil. Here we reported the first attempt to investigate the neurobiology of B. bonariensis venom (BBV) in the insect and mammalian nervous system. BBV (32 μg/g) induced a slow neuromuscular blockade in the in vivo cockroach nerve-muscle preparations (70 ± 4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…The neuromuscular facilitation produced by T. pachyurus venom at low concentrations and the rapid blockade of the twitch responses seen at high concentrations of this venom in PND preparations also were reported for the Brazilian species T. serrulatus [67] and T. bahiensis [70]. The neuromuscular action of scorpion venoms has been mostly associated with the presence of neurotoxins with high affinity for voltage-gated Na + channels [70][71].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The neuromuscular facilitation produced by T. pachyurus venom at low concentrations and the rapid blockade of the twitch responses seen at high concentrations of this venom in PND preparations also were reported for the Brazilian species T. serrulatus [67] and T. bahiensis [70]. The neuromuscular action of scorpion venoms has been mostly associated with the presence of neurotoxins with high affinity for voltage-gated Na + channels [70][71].…”
Section: Discussionmentioning
confidence: 88%
“…The neuromuscular action of T. pachyurus venom demonstrated in this present study comprises the first report with Colombian scorpion species. The action of Tityus venoms on the somatic neurotransmission has been poorly demonstrated in the last decades, with only a few studies reporting their neurotoxic mechanisms in vertebrate nerve-muscle preparations [65][66][67][68][69][70][71]. The neuromuscular facilitation produced by T. pachyurus venom at low concentrations and the rapid blockade of the twitch responses seen at high concentrations of this venom in PND preparations also were reported for the Brazilian species T. serrulatus [67] and T. bahiensis [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also demonstrated that Jbtx caused a significant decrease in the amplitude of muscle and nerve action potentials in a L. migratoria leg preparation, to block muscle twitch. Alterations in the amplitude of a muscle or neuron action potential can be achieved not exclusively, but in part, by the interaction of neurotoxins with six different binding sites of sodium channels (Cestèle & Catterall, 2000;Dong, 2007;dos Santos et al, 2016;Wang & Wang, 2003). Blocking the sodium conductance, a negative shift in the voltage-dependence of activation, slowing down of inactivation or an alteration of ion selectivity are the most common results of the binding of neurotoxins to sodium channels (Stevens et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A barata cinérea pode estar entre as diversas espécies de baratas existentes. Ela também é popularmente conhecida como barata salpicada ou barata lagosta (Ordem: Blattodea, Família: Blaberidae), sendo originaria da África apresentando ampla distribuição geográfica devido a sua fácil associação com seres humanos (SANTOS et al, 2016). A composição química deste inseto varia de acordo com seu estágio de crescimento, apresentando aproximadamente 68,5% de proteína e 22,5% de lipídios em sua fase adulta (LUCAS; OLIVEIRA; PRENTICE, 2019).…”
Section: Introductionunclassified